Studi Efisiensi dan Konservasi Energi Pada Interior Gedung P Universitas Kristen Petra - Stephen Sugiarto Prasetyo; Yusita Kusumarini (Intra, 2016)
This study is accomplished to reveal the efforts of efficiency and energy conservation in East Campus/P Building of Petra Christian University. Energy crisis is the background of this study. The high energy demand in Indonesia is not compensated by enough energy supplies. Furthermore, nearly all of energy supplies in Indonesia is produced from non-renewable resources.One of the high-rise buildings that is fitting to be studied is the East Campus/P Building of Petra Christian University. Energy efficient innovations were applied to the building to reduce the building's energy consumption. The efforts done in P Building needs to be studied and published for public references, also for the improvement of both architecture and interior design specially in high-rise building. This will contribute largely to the efforts of saving the environment and energy saving.The study is done by collecting field data, then it is analyzed using GREENSHIP standards for interior published by Green Building Council Indonesia (GBCI). The result is shown in points and percentage (%) for category of Energy Efficiency and Conservation (EEC). Then, using the result from analysis, conclusion and recommendations can be formulated for future development of energy efficiency in P Building.